Pendidikan dan Masyarakat - Wardani Sihaloho; Maysarah Rabiul Aulia; Ashabul Maimanah; Annisa Hadisti Rahayu; Mastianur Daulay; Zulham Efendi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article discusses the importance of early childhood education and its relationship with society. Challenges such as access to education and lack of knowledge among parents are discussed. The role of the community in supporting early childhood education is emphasized, including providing a conducive environment and material support. Factors such as economic status, cultural beliefs, and social status can influence the relationship between education and society. This article concludes that quality education and a supportive community are essential for optimal development of children, especially in early childhood education. The purpose of this research is to discuss the importance of early childhood education and its relationship with society, as well as challenges and the role of society in supporting early childhood education. Some of the main issues discussed in the research are: 1. The importance of early childhood education and its role in child development. 2. Challenges in accessing early childhood education, such as access and lack of knowledge among parents. 3. The role of the community in supporting early childhood education, including providing a conducive environment and material support. 4. Factors influencing the relationship between education and society, such as economic status, cultural beliefs, and social status. 5. Efforts to increase public awareness about the importance of early childhood education and ensure that all children have access to quality education. Keywords: early childhood education, community, education policy